Structure elucidation and in vitro biological evaluation of sulfated exopolysaccharide from LAB Weissella paramesenteroides MN2C2 - Mai N. Amer, Eman W. Elgammal, Nagwa A. Atwa, Ahmed I. Eldiwany, Insaf E. Dawoud, Ferial M. Rashad (Journal of Applied Pharmaceutical Science, 2021)
The introduction of new bio-product for human diseases treatment is still a great challenge in drug delivery field. This study aimed to extract, purify and characterize exopolysaccharide (EPS) from Weissella paramesenteroides MN2C2 which identified by 16S rDNA under accession number of MK530206 in gene bank. The chemical and spectroscopic analysis using UV, FTIR, NMR and HPLC were applied. The results revealed that the product composed of 80% fructose, 9.3% glucose and 5.6% sucrose with acetyl groups. EDX analysis demonstrated that it formed of high ratios of carbon, nitrogen, oxygen, phosphorous and sulfur. The three-dimensional structure showed irregular compacted lumps with smooth surface. The anticancer activity revealed that the partially purified EPS was strong anticancer agent and highly selective against Colon Caco-2, Breast MCF-7 and Liver HepG-2 cancer cell lines compared to the crude ones. Both EPSs showed antiviral activity (99.99%) against Coxsackie virus (CVB3). Their DPPH antioxidant activity acted in a dose dependent manner. From the obtained results it was concluded that our EPS can serve as a promising candidate for drug delivery.
Keywords: Exopolysaccharides, characterization, Weissella paramesenteroides MN2C2, medical applications.